Nutrient Absorption Rate of Oryzias celebensis Embryo - Yulia Indah Sari Lalombo; Khusnul Yaqin; Sharifuddin bin Andy Omar (Sekolah Tinggi Ilmu Pertanian Wuna, 2021)
Oryzias celebensis is a species of medaka fish in South Sulawesi. During incubation, the growth and development of these fish embryos depend on the nutrients stored in the eggs. Therefore, this study aimed to determine the volume size of egg yolks and oil droplets and the absorption rate of egg yolks of O. celebensis embryos that reared in different incubation media. The study was conducted using a completely randomized design (CRD) with four rearing media treatments, namely A (Early Rearing Media), B (bottled water), C (Pattunuang river water) and D (well water) with five replications . The results showed that the volume of egg yolk and O. celebensis embryo oil in each medium showed a decrease in volume size along with the embryonic development stage. The absorption rate of yolk in O. celebensis embryos in media A had the biggest yolk absorption with an average 0.015±0.038 mm3 while media D had the smallest yolk absorption with an average 0.011±0.022 mm3.